Group Genius - Sawyer, Keith (Ascent Audio, 2008)
Creativity has long been thought to be an individual gift, best pursued alone; schools, organizations, and whole industries are built on this idea. But what if the most common beliefs about how creativity works are wrong? In this authoritative and fascinating new audiobook, Keith Sawyer, a psychologist at Washington University, tears down some of the most popular myths about creativity and erects new principles in their place. He reveals that creativity is always collaborative - even when you're alone. Sawyer's audiobook is filled with compelling stories about the inventions that changed our world: the ATM, the mountain bike, and open-source operating systems, among others. In each case, Sawyer tells the true story of innovation. In spite of the "lone genius" myths that always spring up after an invention's success, these important inventions always originate in collaboration. To understand the hidden collaborations that drive exceptional creativity, Sawyer spent 15 years studying jazz groups and theater ensembles, small businesses, and large corporations. In Group Genius he distills the essence of this acclaimed research and shows us how to be more creative in collaborative group settings, how to change organizational dynamics for the better, and how to tap into our own reserves of creativity. The empowering message is that all of us have the potential to be more creative; we just need to learn the secrets of group genius.